The quadricyclane to norbornadiene radical cation rearrangement: An ab initio and density functional study - Clark, Timothy (Acta Chemica Scandinavica, 1997)
Ab initio and density functional theory have been used to investigate the title reaction. The principles governing radical electrocyclic reactions are summarized and applied to the quadricyclane to norbornadiene radical cation rearrangement. The simple qualitative picture given by this interpretation is then compared with the detailed results of the calculations. In general, the qualitative theories proposed by Bischof and Haselbach provide an excellent conceptual framework for this and other radical electrocyclic reactions. The performance of the different levels of theory is compared and the density functional methods found to underestimate the energy gained from the pseudo-Jahn-Teller distortion away from a symmetrical transition state. Simple BLYP theory fails completely to reproduce this effect and Becke3LYP gives only a small distortion energy. Our best estimate of the activation energy for the rearrangement is less than or equal to 10 kcal mol(-1), in agreement with recent calculations by Each rr al. This value is about twice as high as the current experimental estimate.